Multicultural Education from the Perspective of James A. Banks at Sunan Drajat Islamic Boarding School Lamongan - Lucky Ilham Prayoga; Syafiq Al Faizar; Aulia Dini Afifatusholihah; Binti Fikhratin; Addin Arsyadana (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
This study focuses on the implementation of multicultural education values at the Madrasah Diniyah of Pondok Pesantren Sunan Drajat Lamongan by using the multicultural education dimension approach from James A. Banks. Indonesia, as a country rich in cultural, linguistic, religious, and ethnic diversity, requires an educational model capable of instilling values of tolerance, equality, and respect for differences. Pondok Pesantren Sunan Drajat, established on September 7, 1977, serves as an example of an institution that integrates these values into its education system. This research employs a qualitative method with a descriptive approach, utilizing techniques such as observation, in-depth interviews, and document analysis. The findings reveal that the institution effectively incorporates multicultural values through George R. Terry’s four key management functions planning, organizing, implementing, and controlling. Furthermore, the practice of multicultural education in the pesantren’s early childhood madrasah aligns with James A. Banks’ five core dimensions: content integration, knowledge construction, prejudice reduction, equity pedagogy, and the empowerment of school culture. Values such as inclusivity, tolerance, democracy, and moderation are embodied through learning processes, student activities, and the exemplary behavior of teachers. Thus, this pesantren not only produces students who are knowledgeable and morally upright but also shapes a generation capable of living harmoniously in a pluralistic society. These findings underscore the importance of multicultural education management as a practical strategy for fostering social harmony in diverse Islamic educational institutions.